In vitro characterization of anti-inflammatory activities of 3RS, 7R, 11R-phytanic acid. Issue 1 (23rd February 2023) - Nakanishi, Tomonori; Izumi, Mikihisa; Suzuki, Ryoji; Yamaguchi, Kohta; Sugamoto, Kazuhiro; Erickson, Laurie; Kawahara, Satoshi
Abstract: The aim of the research described here was to investigate the in vitro immunomodulatory effects of 3 RS, 7 R, 11 R -phytanic acid (3 RS -PHY) from the perspective of efficacy against autoimmune diseases. 3 RS -PHY is a milk component with strong agonist activity at the peroxisome proliferator activated receptor (PPAR). As PPAR is a therapeutic target for several human diseases, 3 RS -PHY intake may have possible health benefits. Recently, we chemically synthesized a preparation of 3 RS -PHY and demonstrated that 3 RS -PHY inhibited T-cell production of interferon (IFN)-γ. However, the overall immunomodulatory effects were not evaluated. In this study, mouse splenocytes, purified T-cells and B-cells were stimulated by mitogens and incubated with 3 RS -PHY, followed by evaluation of cytokine and antibody production. A macrophage-like cell line J774.1 was also incubated with 3 RS -PHY to evaluate nitric oxide production. 3 RS -PHY decreased mRNA levels not only of IFN-γ but also of interleukin (IL)-2, IL-10 and IL-17A in splenocytes and similar effects were confirmed at the protein level. In addition, 3 RS -PHY had a direct action on T-cells with preferential inhibitory effects on Th1 and Th17 cytokines such as IFN-γ and IL-17A. Furthermore, 3 RS -PHY suppressed antibody secretion by B-cells and nitric oxide production by J774.1 almost completely, indicating that 3 RS -PHY is a bioactive fatty acid with anti-inflammatory properties. These findings encourage further investigations, including in vivo experiments, to evaluate whether 3 RS -PHY actually shows the potential to prevent autoimmune diseases, and provide basic information to produce milk and dairy products with an increased 3 RS -PHY concentration.